2021
DOI: 10.1038/s41467-021-27084-z
|View full text |Cite
|
Sign up to set email alerts
|

Twofold symmetry of c-axis resistivity in topological kagome superconductor CsV3Sb5 with in-plane rotating magnetic field

Abstract: In transition metal compounds, due to the interplay of charge, spin, lattice and orbital degrees of freedom, many intertwined orders exist with close energies. One of the commonly observed states is the so-called nematic electron state, which breaks the in-plane rotational symmetry. This nematic state appears in cuprates, iron-based superconductor, etc. Nematicity may coexist, affect, cooperate or compete with other orders. Here we show the anisotropic in-plane electronic state and superconductivity in a recen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(81 citation statements)
references
References 58 publications
7
53
0
Order By: Relevance
“…51 Similarly, NMR/NQR experiments point to the Star-of-David CDW at high temperatures, followed by an additional charge modulation below ∼ 40 K. 50 Breaking of the sixfold symmetry of the CDW state was reported experimentally for CsV 3 Sb 5 . 19,52,53 More broadly, the pressuredependent µSR data on the RbV 3 Sb 5 compound also indicates two CDW transitions. 27 Our previous low-temperature, pressure-dependent µSR data on CsV 3 Sb 5 revealed a strong change in the superfluid density within the CDW phase as pressure was varied.…”
Section: Resultsmentioning
confidence: 88%
“…51 Similarly, NMR/NQR experiments point to the Star-of-David CDW at high temperatures, followed by an additional charge modulation below ∼ 40 K. 50 Breaking of the sixfold symmetry of the CDW state was reported experimentally for CsV 3 Sb 5 . 19,52,53 More broadly, the pressuredependent µSR data on the RbV 3 Sb 5 compound also indicates two CDW transitions. 27 Our previous low-temperature, pressure-dependent µSR data on CsV 3 Sb 5 revealed a strong change in the superfluid density within the CDW phase as pressure was varied.…”
Section: Resultsmentioning
confidence: 88%
“…This "nematic"-like C 3 -symmetry broken phase could be stabilized on the surface, which is predicted for a real CDW ordering with k z = 0 due to the three dimensional coupling [8]. It might explain the rotational symmetry breaking due to uniaxial charge modulation observed by STM [15,16,22], two-fold c-axis magnetoresistance below T S [40,41], the enhanced m 11 − m 12 elasto-resistance coefficient above T S [55], as well as the two-fold-like amplitude of coherent phonon mode observed in the pump-probe Kerr rotation measurement [39].…”
Section: The Symmetry Of the Order Parametersmentioning
confidence: 76%
“…Furthermore, at an intermediate temperature T * about 60-70 K, an additional uniaxial 1 × 4 charge modulation was reported by STM studies [15,16,22]. Ultrafast coherent phonon spectroscopy measurements [37][38][39], muon spin relaxation measurements [34], and transport studies [40,41] all identified anomalies at around T * , suggesting a secondary instability below T S . Finally, density functional theory (DFT) phonon dispersion calculations found negative phonon frequencies at both M (1/2, 0, 0) and L(1/2, 0, 1/2) points [21], as well as at points along the U -line connecting the M and L momenta of the Brillouin zone for the high-temperature phase [11], indicating M + 1 , L − 2 , and U 1 lattice instabilities.…”
mentioning
confidence: 86%
“…Here, the presence of linear bands, Dirac points, and band saddle points (van Hove singularities) in the electronic structure of a nearest-neighbor kagome metal causes multiple electronic instabilities that have been studied theoretically [1][2][3][4] but did not find their way into the lab until the recent discovery of the AV 3 Sb 5 compound family with A = K, Rb, Cs [5]. Both charge-density wave (CDW) order [6][7][8][9][10][11] and superconductivity [12][13][14][15][16][17] observed experimentally in these compounds closely resemble theoretical findings for a simple kagome metal with the Fermi energy lying near the van Hove singularity at the filling level of 5 12 [18,19]. In AV 3 Sb 5 , the corresponding saddle points are clearly visible in the vanadium bands around the M point slightly below the Fermi level (Fig.…”
Section: Introductionmentioning
confidence: 99%